The association between COVID-19 lockdown and disease severity, quality of life, and mental health in patients with psoriasis: a cross-sectional study in Southwestern China - Shao, Xinyi; He, Wenyan; Chen, Aijun; Kapur, Sahil; Cruz, Jeffrey; Wang, Ping (Frontiers in Public Health, 2025)
BackgroundOur study aimed to clarify the impact of home quarantine on disease severity, quality of life, and mental health in psoriasis patients through the multidimensional analysis of the status of home quarantine, the severity of psoriasis, quality of life, and depression scores during the COVID-19 pandemic.MethodsFrom 2022 to 2023, we conducted telephone follow-up on 963 psoriasis patients. Participants’ demographic characteristics, psoriasis condition, home quarantine duration, quality of life and depression symptom scores were collected. The association between COVID-19 lockdown and patient-reported outcomes were investigated with pearson correlation and Spearman correlation.ResultsA total of 963 participants were recruited, finally 605 participants were enrolled. The mean values of age and disease duration was 43.63 years, 312.35 years, 67.6% were male. Patients with disease-related impaired quality of life (DLQI > 5) accounted for 7.44%. A total of 65 patients had varying degrees of depression symptoms (QIDS-SR16 > 5 points). The result of correlation analysis revealed a positive correlation between BSA and both DLQI and QIDS-SR16 scores (R = 0.27, p < 0.001; R = 0.08, p < 0.05).ConclusionOur results revealed that COVID-19 lockdown had a measurable impact on disease severity, quality of life, and mental health in psoriasis patients. Many individuals experienced varying degrees of symptoms aggravation during the lockdown. The severity of psoriasis was negatively correlated with quality of life and positively correlated with depression symptoms, with older adult patients being particularly vulnerable to depression. These findings highlight the importance for dermatologists to integrate mental health assessment and support into routine psoriasis management.